STORY MAPPING STRATEGY TO IMPROVE STUDENTS’ READING SKILL AT SMP AN-NUR WATUKOSEK PASURUAN - Isnani, Zakiya (E-Link Journal, 2021)
The main purpose of this research is to know the improvement of students’ reading skill in narrative text through story mapping strategy. this research was conducted at SMP An- Nur Watukosek-Pasuruan. this research is a classroom action research which is conducted in two cycles. this study was carried out on February to April 2021. the subjects were the eight grade students of SMP An-Nur Watukosek, Pasuruan. The data collection involved a number of instruments, namely preliminary test to know the reading ability firstly. Then, using post-test in the end of each cycle, questionnaires, and also an interview. The post-test used in each cycle to know the reading’s improvement after using story mapping strategy. The questionnaire in the form administrated to collect data about the students’ appreciation in learning reading using story mapping, both the teacher’s method, the students, and also story mapping itself. There were several steps in this research implementation, they are identifying the problems, planning, acting, observing and reflecting.the result showed that the students’ reading ability improved and the target of this research was achieved. And also they felt  easier to understand the text, because it consist of some elements, are orientation, complication, and resolution.. Keywords: Story mapping, reading skill